Mehanizmi razvoja bakterijske odpornosti na antibiotike - Zidar, Nace (Farmacevtski vestnik, 2019)
Occurrence of resistance of the most prevalent bacterial pathogens to antibiotics is one of the major threats to public health. The main reasons for the lack of effective antibiotics have been the misuse of those agents and the unavailability of newer drugs. Bacteria adapt to antibiotics using two main strategies: with mutations of genes that are associated with the action of antibiotics or with the acquisition of foreign DNA coding for such genes. There are several mechanisms for the development of antibiotic resistance, which include prevention of access to drug targets, changes in the structure of antibiotic targets and direct modification of antibiotic structures. It is important to understand these mechanisms in order to successfully design new antibacterial drugs with a lower probability for resistance development. Because the terms have become interchangeable, for the purpose of this article, the term antibiotic is used as a synonym for an antibacterial drug.
Keywords: Antibiotiki; bakterijska odpornost; Bakterijska rezistenca; izlivna črpalka; mutacija; protibakterijska učinkovina